Pelatihan Mikrotik Untuk Peningkatan Kompetensi Administrasi Jaringan Komputer untuk Persiapan Sertifikasi MTCNA Bagi Siswa SMKS Siti Banun - Purnama, Iwan; Bangun, Budianto; Lubis, Rizky Ramadhan Hasan; Sakinah, Sakinah (HIMPUNAN DOSEN GEMILANG INDONESIA, 2022)
Computer networks are one of the important subjects in the field of Information Technology. Various types of computer network devices continue to innovate to adapt to technological developments. Mikrotik is a router product that is widely used to implement a network system. As educators at Vocational High Schools, especially in the Computer and Network Engineering major, students are expected to be able to increase their understanding in the field of computer networks using proxy. Mikrotik training is given to students at SMKS Siti Banun Sigambal to be able to implement a network system and can become a trainer to be able to teach about proxy at school. This training is used to prepare students for certification regarding basic network systems or Mikrotik Certified Network (MCTMA). The training methods used are lectures and practice (demonstrations). The results of the training activities in outline include several components of success, namely: 1) The success of the training/participants in the training, 2) The achievement of the planned research objectives, 3) The achievement of the planned material objectives.